Sclerotherapy for Intra-abdominal Lymphatic Malformations in Children - Russell, Katie W.; Rollins, Michael D.; Feola, G. Peter; Arnold, Ryan; Barnhart, Douglas C.; Scaife, Eric R. (European Journal of Pediatric Surgery, 2014)
Purpose Sclerotherapy is well described as a treatment for lymphatic malformations (LMs) in the head, neck, and other soft tissue areas. This study aims to evaluate the effectiveness of intralesional sclerotherapy as primary treatment for intra-abdominal LMs in children.Methods We conducted a retrospective review from 2008 to 2012 of all children with intra-abdominal LMs treated with sclerotherapy at our tertiary children's hospital.Results In this study, five patients underwent sclerotherapy as a primary intervention for intra-abdominal LMs. The ages of these patients ranged from 12 to 52 months at the time of initial treatment. Doxycycline was used as the primary sclerotherapy agent. The patients required between three and five (median 3) sclerosing treatments over a period that ranged from 5 to 366 days (median 28). No child has required an operation and all LMs have decreased in size. The median decease in maximum diameter is 62% (21–67). Complete resolution has not been attained but all have experienced symptomatic relief with a median follow-up of 3 (1–24) months.Conclusions Sclerotherapy is an effective first-line therapy for intra-abdominal LMs in the pediatric population and should be considered when treating these difficult lesions.
Keywords: sclerotherapy; lymphatic malformation; doxycycline; pediatrics